Short Term Clinical and Angiographic Outcome of Skeletonized Harvesting Technique of Left Internal Mammary Artery, Compared to Pedicled Harvesting for Coronary Revascularization - Sazzad, Md Faizus (Bangladesh Journals Online (JOL), 2019)
10.3329/uhj.v12i2.36388